2011
DOI: 10.1080/00207543.2010.519735
|View full text |Cite
|
Sign up to set email alerts
|

Interpretive structural modelling of risk sources in a virtual organisation

Abstract: Speedier network decision making together with shorter time to bring items to market together with lower network operating costs all result from enhanced knowledge sharing. In addition re-use of enterprise and network knowledge resulting from improved capture means that any risk of repeating earlier project work is limited, repetition of past mistakes is reduced. Decisions are made with greater awareness of any risks involved and therefore there is likely to be a reduction in costs arising from faulty decision… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
50
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(56 citation statements)
references
References 57 publications
0
50
0
Order By: Relevance
“…It represents complex system in a visual hierarchical structure (Chang et al 2013;Borade and Bansod 2012) and transforms unclear, poorly articulated mental models of a system into visible, well defined hierarchical models (Alawamleh and Popplewell 2011;Jain and Raj 2015;Sindhwani and Malhotra 2016). ISM is primarily as a group learning process as interrelations among variables under study are decided based on group judgement (Gothwal and Raj 2015), but individuals may also apply it (Ravi and Shankar 2005;Faisal et al 2007).…”
Section: More Reliance On Imported Devices Leading To Increased Importsmentioning
confidence: 97%
“…It represents complex system in a visual hierarchical structure (Chang et al 2013;Borade and Bansod 2012) and transforms unclear, poorly articulated mental models of a system into visible, well defined hierarchical models (Alawamleh and Popplewell 2011;Jain and Raj 2015;Sindhwani and Malhotra 2016). ISM is primarily as a group learning process as interrelations among variables under study are decided based on group judgement (Gothwal and Raj 2015), but individuals may also apply it (Ravi and Shankar 2005;Faisal et al 2007).…”
Section: More Reliance On Imported Devices Leading To Increased Importsmentioning
confidence: 97%
“…ISM is a tool which permits identification of structure within a system (Jadhav et al 2014a;Kumar et al 2013a, b;Raj et al 2010;Rajesh et al 2007;Solanki and Choudhary 2014). ISM is used for identifying and summarizing the relationship amongst the variables related to an issue or problem by developing a well-defined model (Alawamleh and Popplewell 2011;Attri et al 2013;Charan et al 2008;Eswarlal et al 2011;Faisal 2010;George and Pramod 2014;Kannan et al 2008;Ravi and Shankar 2005). Thakkar et al (2008) compared three contemporary modelling techniques: analytic hierarchy process (AHP), analytic network process (ANP), and interpretive structural modelling (ISM) and found that ISM has a higher capability to capture dynamic complexity.…”
Section: Interpretive Structural Modelling (Ism)mentioning
confidence: 99%
“…Although one of the main reasons for establishment of VO is knowledge and information sharing, potential risk [14] arises in limited transfer of knowledge. In [10] it is emphasized that, in case when the agreement between entities is not o cial, the boundaries of rights, obligations, commitment are blurred; before a network is established, members-future partners have to achieve consensus about terminology, terms of use, obligations in order to prevent future misunderstandings.…”
Section: Challenges For Human Resources In Virtual Organizationsmentioning
confidence: 99%
“…According to [10], an ethical problem might appear when one partner-entity takes part-bids in two or more VO in terms of resources, or sta .…”
Section: Challenges For Human Resources In Virtual Organizationsmentioning
confidence: 99%